Janus Quasi-Solid Electrolyte Membranes with Asymmetric Porous Structure for High-Performance Lithium-Metal Batteries - Zerui Chen; Wei Zhao; Qian Liu; Yifei Xu; Qinghe Wang; Jinmin Lin; Hao Bin Wu (Nano-Micro Letters, 2024)
Highlights Janus quasi-solid electrolyte membranes with asymmetric porous structure were constructed, showing a high σLi+ of 1.5 × 10-4 S cm-1 and a high t + of 0.71. The solvation structures and ion transport dynamics in nanopores have been deciphered, manifesting a concentrated electrolyte-like structure and regulated transport behaviors. Quasi-solid NCM 622||Li cells have been demonstrated to stably cycle for 200 cycles at 1 C, and pouch cell has shown high tolerance for abuse.